Influence of the “off the street, on the ball” midnight football program on physical fitness, self-esteem and quality of life in youth-at-risk / Lim Boon Hooi, Abdul Halim Mokhtar and Balbir Singh Gill - Lim, Boon Hooi; Mokhtar, Abdul Halim; Gill, Balbir Singh (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2012)
The main aim of this study was to investigate the influence of the “Off the Street, On the Ball” Midnight Football Program on physical fitness components, self-esteem and perception on quality of life between baseline and post-program in youth-at-risk. A total of 58 male participants in the pilot project “Off the Street, On the Ball” Midnight Football Program organized by the Social Responsibility Department, Asian Football Confederation (AFC) were recruited as the subjects of this study. They were aged 14-19 years, with a mean age of 16.72 (SD= 1.24) years. Instrumentations employed in this study were Yo-Yo Intermittent Test, Single Sprint Test, and Balsom Agility Test to measure aerobic endurance, speed and agility of the subjects on baseline and post-program. Two questionnaires were administered, the Influence on Quality of Life Scale (IQLS) and Rosenberg Self-Esteem Scale (RSES) to collect perception on quality of life and self-esteem on baseline and post-program. Between the baseline and post-program, all subjects were divided into eight groups followed four weeks of soccer-specific periodized training programme and controlled by certified coach assigned to them. Results of present study revealed that all physical fitness components (aerobic endurance, speed and agility) were significant difference between baseline and postprogram at p < .05. For the self-esteem, results indicated significant differences favouring the post-program (t=-19.82, df=91, p<.05). An analysis of the individual items on the IQLS indicated that vast majority of the subjects either agreed or strongly agreed that involvement in the midnight football program positively influenced their perception on quality of life. Overall, the results of the current study lend additional support to the use of football program to develop positive self-esteem and creating opportunities to experience positive perception on quality of life. Thus, positive self-esteem and positive perception on quality of life are significantly more likely to reduce social risk factors for juvenile delinquency and serious antisocial behaviour in youth-at-risk in Asia, especially in Malaysia.